Analisis Pengaruh Penggunaan Asuransi Contractor All Risk, Bunga Bank, dan Bagi Hasil Terhadap Pengalihan Potensi Risiko pada Proyek Konstruksi - Doni Setio Prastowo (Syntax Corporation Indonesia, 2023)
Implementation of a construction project will give rise to various kinds of risks during its work, so risk management is needed to reduce and transfer risks that will occur during construction project work. One alternative risk transfer to reduce potential risks in construction projects is to use Contractor All Risk Insurance (CAR), which is one of the engineering insurance products issued by general insurance companies, especially by general insurance companies in Indonesia. This research aims to test the influence of the variables Use of CAR Insurance (X1), Bank Interest (X2), and Profit Sharing (X3) on Reducing Potential Risks on Construction Projects (Y3). The research locations are 20 construction service companies in Jakarta, which use CAR insurance. The population of this research is employees who work at these 20 companies. The number of samples was 220 respondents. The sampling technique is purposive sampling. The primary data collection technique is through survey techniques with a 1-5 Likert Scale questionnaire as the research instrument. Secondary data collection techniques using document and literature studies. The data analysis technique uses Structural Equation Modeling (SEM), with Lisrel 8.80 software. The research results show that the three independent variables, namely Use of CAR Insurance (X1), Bank Interest (X2), and Profit Sharing (X3) partially have a positive and significant effect on Reducing Potential Risks in Construction Projects (Y3).